Identificação de hemoglobinas com corrida eletroforética semelhante à da hemoglobina S no Programa Estadual de Triagem Neonatal de Minas Gerais (PETN-MG) - Fernanda Silva Pimentel (2010)
Introduction: Newborn screening is crucial for the identification of children with HbS. The incidence of sickle cell disease in MG is 1:1,400. There are at least 3 beta and 4 alpha globin variants whose isoeletric focusing point is similar to that of HbS, which may lead to false positive diagnosis of sickle cell trait or disease. Objectives: a) to discriminate HbS from variants with similar IEF properties; b) to sequence a variant found in 2 homogygous children, c) to assess the clinical meaning of thos variant. Methods: 126 children who had newborn screening results read as indeterminate and confirmation IEF at age 6 months showing a variant with HbS mobility were studied. New samples were collected and IEF gels were independently read in duplicate by 3 observers. Variants were tentatively classified as faster (+0.5mm), indistinguishable or slower (-0.5mm) than a HbS-control. Allele-specific PCR for S-gene was done in all cases and multiplex PCR for 7 Ñ-thalassemia deletions were done in homozygous cases. Alpha-globin genes were sequenced in both cases and beta-gene, in the first case. NCBI NG_000006.1 was the reference sequence for the gene. Results: 62 children were originally diagnosed by the program as AS; 62 AV, and 2 VV (V=rare Hb). From 756 readings (126x3x2=756) Hbs were classified as faster than control-S in 56.7%, slower in 5.4% and indistinguishable in 35%. The intra-observer agreements varied from 63.2-77.5%. Triple inter-observer agreement was only 23.3%. In 12 cases (9.5%) PCR S-gene was positive; blind IEF pattern was faster in 29% of readings and indistinguishable from S in 71%. Families of the two homozygous children were not related to each other. Consaguineous marriage was present in both families. IEF in both children yielded a single band with HbS mobility. Parents IEF looks like AS phenotype. Sickle preps and ÒS allele-specific PCR were all negative. Ò-gene sequencing in the first family was normal. Multiplex PCR for Ñ-thalassemia deletions disclosed that both children were -3.7/-3.7 and all parents /-3.7. Hybrid 3.7 gene sequencing showed mutation in codon 78 (AAC>AAA; Asn>Lys; Hb Stanleyville-II), homozygous for both children and heterozyzous for all parentes. Type I 3.7 hybrid gene was detected throughout: crossover had ocurred 5 of Apa-I restriction site in IVS 2 of the primitive 1-gene. Both children had mild mycrocytic and hypochromic anemia, as expected for -3.7/-3.7 patients. Conclusions: The proposed IEF classification for S-like Hb is misleading. Many IEF indistinguishable variants were proved not being Hb S. Some true Hb S were read as faster than S. True Hb S, however, was never read as a slower Hb and thus is a good hint for the differential diagnosis. Molecular methods will elucidate the rare variants. In one of these both children had homozygous Ñ3.7 thalassemia (type I) associated with Hb Stanleyville-II (Ñ78 AsnLys), in homozygous state (Ñ2Staß2). Parents were heterozygous for both mutations. Mycrocytosis and hypochromia represent the typical picture of Ñ-thalassemia-1.